Peran Kepemilikan Institusional dalam Memoderasi Pengaruh Kinerja Lingkungan, Paparan Media dan Leverage terhadap Pengungkapan Emisi Karbon - Tianisyah Mi’raz, Raffa; Dwi Astuti , Christina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the role of institutional ownership in moderating the environmental performance, media exposure, and leverage on carbon emission disclosure by incorporating firm size, age, and Stakeholders as control variables. The study utilizes a quantitative approach, analyzing secondary data, and focuses on companies in the energy sector, basic material sector, industrial sector, consumer non-cyclicals sector, and infrastructure sector listed on the Indonesia Stock Exchange from 2019 to 2022. Using purposive sampling, 165 observation samples were collected between 2019 and 2022. Data analysis employed multiple linear regression analysis using the SPSS program. The findings indicate that environmental performance and media exposure positively influence carbon emission disclosure, while leverage does not have a significant impact on carbon emission disclosure. Institutional ownership can strengthen the influence of media exposure on carbon emission disclosure but cannot reinforce the effect of environmental performance or weaken the impact of leverage on carbon emission disclosure.